National voice: A discourse analysis of China Central Television's News Simulcast. (August 2013) - Feng, Debing
News Simulcast, the flagship news program for China Central Television (CCTV), has been widely studied by Chinese scholars. However, little attention has been paid to its representation of ideological meanings. To address this issue, the present study, drawing upon Van Dijk's (1988b) framework of three-level analysis of discourse structure, carries out a comprehensive discourse analysis of the news broadcast on this program. A corpus of 10 episodes of News Simulcast was selected as the database, from which a subset of four episodes were thoroughly examined from the macro-level of discoursal and thematic structure to the micro-level of linguistic and semiotic structure. It demonstrates that, due to its historic background and political privilege, News Simulcast broadcasts news with an authoritative national voice, speaking primarily in the interests of the Communist Party, the government and the people, and it thus forms a rather stereotyped discourse structure: positive 'us' versus negative 'them'.